Innovation Pattern Heterogeneity and Firm Strategic Agility: Push- and Pull-Effects of COVID-19 on Firms’ Innovation Strategies - Marina Rybalka (Businesses)
The coronavirus crisis hit both the world and national economies hard. By using a structural equation modelling (SEM) approach and microlevel data from the Community Innovation Survey (CIS2020) on a representative sample of 6437 Norwegian firms comprising a set of COVID-19-related questions, this paper explores the role of firms’ innovation capabilities and strategic agility in times of crises. Our main hypothesis is that these two concepts are interrelated. More specifically, this paper investigates the ‘push’ and ‘pull’-mechanisms of the pandemic on firms’ innovation strategies, as well as which firms were most agile, adapted quickly, introduced innovation due to the COVID-19 crisis rapidly and became more effective with respect to their pre-crisis innovation capabilities. The results indicate that both mechanisms were active during the coronavirus crisis, and most of the firms carried out strategic reactions and changed their business operations on along-term basis. However, the results for innovation output and efficiency improvements vary significantly. “Process developers”, “active R&D doers” and “radical innovators” (the firms that are persistent innovators with the highest score on performing in-house R&D continuously and on innovating in the pre-crisis period) are found to be most agile during the pandemic. They had both introduced innovation and improved their efficiency in quick response to COVID-19. However, firms with low innovation capabilities demonstrated poorer performance during the crisis. These results imply that pre-existing innovation capabilities are important for firms’ strategic flexibility during crises and their ability to respond to changes quickly and efficiently.